2012
DOI: 10.1016/j.neuron.2012.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Excessive Activation of mTOR in Postnatally Generated Granule Cells Is Sufficient to Cause Epilepsy

Abstract: Summary The dentate gyrus is hypothesized to function as a “gate”, limiting the flow of excitation through the hippocampus. During epileptogenesis, adult-generated granule cells (DGC) form aberrant neuronal connections with neighboring DGC, disrupting the dentate gate. Hyperactivation of the mTOR signaling pathway is implicated in driving this aberrant circuit formation. While the presence of abnormal DGC in epilepsy has been known for decades, direct evidence linking abnormal DGC to seizures has been lacking.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
267
2
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(284 citation statements)
references
References 63 publications
(86 reference statements)
14
267
2
1
Order By: Relevance
“…Interestingly, the evolution of seizures and autistic behaviors following neonatal brain injury may be mTOR dependent (Talos et al 2012). Transgenic Pten deletion in dentate granule cells (DGCs) induces mTOR activation and leads to spontaneous seizures (Pun et al 2012). Interestingly, a recent study suggested that in Tsc1 knockout cells, although the frequency of mESPCs was increased, excitability of the network resulted from diminished inhibitory drive with decreased amplitude and frequency of miniature inhibitory postsynaptic currents (Bateup et al 2013).…”
Section: Mtor Malformations and Epileptogenesis: Distinct Mechanistmentioning
confidence: 99%
“…Interestingly, the evolution of seizures and autistic behaviors following neonatal brain injury may be mTOR dependent (Talos et al 2012). Transgenic Pten deletion in dentate granule cells (DGCs) induces mTOR activation and leads to spontaneous seizures (Pun et al 2012). Interestingly, a recent study suggested that in Tsc1 knockout cells, although the frequency of mESPCs was increased, excitability of the network resulted from diminished inhibitory drive with decreased amplitude and frequency of miniature inhibitory postsynaptic currents (Bateup et al 2013).…”
Section: Mtor Malformations and Epileptogenesis: Distinct Mechanistmentioning
confidence: 99%
“…In addition to the question of how abGCs might contribute to human cognitive abilities, the utility of targeting adult neurogenesis for the treatment of psychiatric and neurological diseases is also at stake. Animal model studies have suggested that aberrant adult neurogenesis might contribute to the pathophysiology of depression and stress responses (Schloesser et al 2009;Snyder et al 2011;Dranovsky and Leonardo 2012), the response to antidepressants (Santarelli et al 2003), post-traumatic stress disorder and anxiety (Kheirbek et al 2012b), epilepsy (Parent et al 1997;Scharfman et al 2000;Pun et al 2012), schizophrenia (Kvajo et al 2008(Kvajo et al , 2011Christian et al 2010), Alzheimer's disease (Galvan and Bredesen 2007;Mu and Gage 2011), drug addiction (Mandyam and Koob 2012), and Fragile X syndrome (Guo et al 2011). Although it seems unlikely that adult neurogenesis will critically contribute to all of these disorders, there are certainly grounds to anticipate that ways of successfully manipulating adult neurogenesis will find clinically beneficial uses.…”
Section: The Mammalian Dentate Gyrusmentioning
confidence: 99%
“…Given concerns about off-target effects of shRNA (Kaelin 2012), a complementary strategy is the use of inducible NSC-specific Cre-recombinase in animals carrying floxed genes of interest (e.g., Kheirbek et al 2012a;Pun et al 2012).…”
Section: Afferent Synaptic Connectivitymentioning
confidence: 99%
“…A forebrain-specific deletion of PTEN from excitatory neurons (NEX-PTEN) results in early lethality and enlargement of the forebrain, although no seizures were reported (Kazdoba et al 2012). In contrast, selective deletion of PTEN in dentate granule neurons results in epilepsy within a month (Pun et al 2012). …”
Section: Models Of Mtor Dysregulationmentioning
confidence: 99%